Spatial implications of transport pricing - Graham,DJ; Glaister,S (J TRANSP ECON POLICY, 2006)
This paper describes spatial effects of transport pricing in England. It presents detailed results from a model developed to test the effects of a range of charging scenarios across England. In developing these scenarios we make use of estimates of the marginal social costs of travel, exploring revenue raising and revenue neutral charging options. For each scenario, model results describe changes in traffic volumes and traffic speeds at a detailed spatial level. The results show that transport pricing can be used to effectively reduce traffic in congested times and places, and where environmental damage is greatest, while allowing other areas to enjoy the benefits of greater mobility at lower cost.